2015
DOI: 10.5732/cjc.014.10124
|View full text |Cite
|
Sign up to set email alerts
|

Use of subsequent PET/CT in diffuse large B-cell lymphoma patients in complete remission following primary therapy

Abstract: Interim 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (I-PET/CT) is a powerful tool for monitoring the response to therapy in diffuse large B-cell lymphoma (DLBCL). This retrospective study aimed to determine when and how to use I-PET/CT in DLBCL. A total of 197 patients treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) were enrolled between October 2005 and July 2011; PET/CT was performed at the time of diagnosis (PET/CT0), after 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Of the patients with negative PET-CT results, 13.0% had died within the 3-year follow-up period as compared to 43.8% of patients with positive PET-CT results who died in the same period. These results are consistent with those described by Xu and Wei [25] and Mamot et al [26]. However, Mamot et al [26] analyzed 92 patients with DLBCL and reported a recurrence rate of 39.1% in patients with a negative interim PET-CT, which is similar to the recurrence rate of 30%-40% observed after treatment [27, 28].…”
Section: Discussionsupporting
confidence: 82%
“…Of the patients with negative PET-CT results, 13.0% had died within the 3-year follow-up period as compared to 43.8% of patients with positive PET-CT results who died in the same period. These results are consistent with those described by Xu and Wei [25] and Mamot et al [26]. However, Mamot et al [26] analyzed 92 patients with DLBCL and reported a recurrence rate of 39.1% in patients with a negative interim PET-CT, which is similar to the recurrence rate of 30%-40% observed after treatment [27, 28].…”
Section: Discussionsupporting
confidence: 82%
“…refractory and relapsed pts. : IVAC +ASCTKong et al (2016) [37]Retrospective105100 % 56 (19–82)54.3 % 43.8 % R-CHOPNRNRMikhaeel et al (2016) [38]Retrospective147100 % 57 (22–86)49.7 % 68.7 % R-CHOPStage I/II non-bulky: 3-4× R-CHOP and IFRT34.0 % Not upfront ( n  = 1 after clinical progression)Mamot et al (2015) [39]Prospective125 b /138100 % 58.4(18-81) c 54.3 % c 53.6 % c R-CHOP14 d + 2R17.4 % c =eventNRZhang et al (2015) [40]Retrospective197100 % 46 (18–81)60.4 % 59.4 % 14.2% R-CHOP14 d 85.8% R-CHOP21 a 18.8 % Not upfront ( n  = 1 progression at end-of-treatment)Carr et al (2014) [41]Prospective327 b /361DLBCL:97.2 % PMBCL:2.8 % 55 (IQR 44–64)52.9 % 64.2 % (R-)CHOP21 a MACOP-B ( n  = 1)R-CNOP ( n  = 4)86% R20.2 % NRDabaja et al (2014) [42]Retrospective294 b /350100 % 49% > 6155.4 % 62.6 % 82.0% R-CHOP11.2% R-HCVAD6.8% other29.9 % NRMylam et al (2014) [43]Prospective112100 % 62 (23–85)52.7 % 82.0 % 84.8% R-CHOP9.8% R-CHOEP5.4% other(92.9% R55% 14 day45% 21 day)In methods but no numbersNRNols et al (2014) [44]Retrospective73100 % 60 (18–85)63.0 % 68.5 % 15.1% R-CHOP14 d 49.3% RCHOP21 a 11.0% R-mini-CHOP23.3% R-ACVBP1.4% CHOPNR8.2%Fuertes et al (2013) [45]Prospective50100 % 55 (21–79)56.0 % 44.0 % R-CHOP21 a NRNRGonzalez-Barca et al (2013) [46]Prospective69100 % 60 (18–78.9)53...…”
Section: Resultsmentioning
confidence: 99%
“…Interim PET/CT can be used as a predictive marker for prognosis with PET response in the interim denoting better outcomes. In a study [57] negative PET/CT after 2 cycles when compared to those who had positive scans, showed significantly higher CR (…”
Section: Role Of Pet/ct In Management Of Dlbclmentioning
confidence: 97%
“…The regimen is a dose adjusted regimen combining etoposide, prednisone, vincristine, cyclophosphamide and doxorubicin in an infusional manner targeting prolonged drug exposure to reduce resistance and dynamic dose adjustments allowing for highest acceptable doses. [75][76][77][78][79][80][81][82][83]) was higher as compared to chemo alone arm (59% [54][55][56][57][58][59][60][61][62][63][64]) and 3year overall survival (OS) in R-chemo arm was also higher than the chemo alone arm (93 vs. 84%) [62]. The SWOG S0014 study [63] was a phase II study where patients with limited stage disease and at least 1 adverse feature, based on stage modified-IPI were given rituximab with 3 cycles of CHOP followed by involved field radiation therapy (IFRT).…”
Section: Double-/triple-hit Lymphomamentioning
confidence: 99%